Photovoltaic Energy Variations Due to Roofing Choice. (2016) - Alshayeb, Mohammed; Chang, Jae D
Abstract: Roofs comprise 20-25% of the total urban surface area and with different roofing technologies and photovoltaic, present an opportunity for sustainable building designs. The operation temperature of photovoltaic (PV) modules has a significant impact on the conversion efficiency and output energy of the PV system. This research investigated the thermal interactions between the building envelope and PV panels by examining the PV panel temperature differences for those installed over a green roof (PV-green) and those installed over a black roof (PV-black). A LEED platinum certified educational building with roof mounted PV panels was used as a case study for the experimental phase of the study. PV panels over the green roof consistently recorded lower temperatures than PV panels over the black roof. Therefore, the PV panels over the green roof had more energy output compared to the PV panels over the black roof.